Multilocus Sequence Analysis highlights genetic diversity of Acidovorax avenae strains associated with sugarcane red stripe - Fontana, Paola Daniela (2019)
XXX Congress of the ISSCT (International Society of Sugar Cane Technologists), Tucumán, from 31 August to 8 September 2019